1998
DOI: 10.1021/jp983181o
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Polyene Dynamics in Solution:  The Conformational Relaxation and Thermalization of Highly Excited cis-1,3,5-Hexatriene as a Function of Initial Conformation and Solvent

Abstract: Femtosecond transient absorption spectroscopy has been used to investigate the ground and excited-state dynamics of cis-1,3,5-hexatriene (Z-HT) and 1,3-cyclohexadiene following excitation to the strongly allowed 1B state in cyclohexane and n-hexadecane solvents. The internal conversion from the excited state manifold to produce vibrationally excited ground electronic state Z-HT occurs with rates of ca. 2−4 ps-1. The relaxation of highly excited Z-HT is used to probe the solvent−solute interaction and the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
75
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(79 citation statements)
references
References 60 publications
(186 reference statements)
4
75
0
Order By: Relevance
“…These studies have found that the conical intersection-mediated ring-opening step in isomerization is completed in less than 200 fs [22], after which the molecule undergoes conformational changes on a range of timescales (see inset in Fig. 1) [26,27]. We observe a clear signature of the isomerization in the fragmentation signal.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…These studies have found that the conical intersection-mediated ring-opening step in isomerization is completed in less than 200 fs [22], after which the molecule undergoes conformational changes on a range of timescales (see inset in Fig. 1) [26,27]. We observe a clear signature of the isomerization in the fragmentation signal.…”
mentioning
confidence: 59%
“…An increase in the production of H + in HT compared to CHD had also been observed in x-ray fragmentation experiments on the stable CHD and HT isomers (a mixture of tZt and tEt forms in case of HT), performed at the Advanced Light Source synchrotron (to be published separately [32], also see The relative change in the ion-KER from before to after UV excitation should in principle provide information about the evolution of the geometry and the kinetic energy of the nuclei during the isomerization. In the x-ray experiment the kinetic energy and the ion count increase on a timescale considerably longer than electronic excitation, but consistent with subsequent conformational changes that the excited molecule undergoes after the ring opening [26,27] and possible other reactions of the hot product and educt in the ground state [28]. At present, it is difficult to separate different contributions to the observed signal.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…In reactive systems, where bonds are broken and formed, the partitioning of energy may result in its localization in certain bonds associated with the reaction coordinate. Indeed, we observed incomplete energy partitioning even up to 400 ps in hot 1,3,5-hexatriene (HT), formed by the ultrafast ring opening of CHD (25)(26)(27)(28). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In solution, this energy is dissipated to the bath, cooling the internal temperature from an estimated 2200 K to the ambient temperature of the surroundings. 12 Interest in this reaction is driven by its role as a model system for modern mechanistic photochemistry. [9][10][11] The CHD ringopening is a prototypical pericyclic reaction and has contributed to the development and corroboration of the Woodward-Hoffman rules, 13 which predict the stereochemical outcome for pericyclic reactions by correlating the first excited state of the reactant with the first excited state of the product and the ground state of the reactant with a doubly excited state of the product, and vice versa.…”
Section: Introductionmentioning
confidence: 99%